Torture and torturous violence : transcending definitions of torture - Canning, Victoria (Bristol University Press, 2023)
With growing acknowledgement that torture is too narrowly defined in law, this book offers a nuanced reflection on the definition of torturous violence and its implications for survivors. Drawing on a decade of research with psychologists and women seeking asylum, Canning sets out the implications of social silencing of torture.